Krisis Lingkungan Berskala Internasional dalam Perspektif Fiqh Ekologi - Habibi, Muhammad; Nabilah, Febriana (Medan Resource Center, 2024)
Humans, as stewards of the earth, are entrusted with the responsibility of preserving environmental balance through the use of reason and conscience, which collectively form international ecological wisdom. Environmental preservation becomes effortless and natural when rooted in everyday human practices, ensuring the sustainability of nature without the need for punitive measures or external enforcement. This paradigm is explicitly reflected in the nation's constitution, particularly in Article 33, paragraphs (3) and (4) of the 1945 Constitution, which encapsulates the principle of a